(untitled) (Research, Society and Development, 2021)
The training of teachers makes up the path for the construction of the social development of subjects through education, dealing with the formative conceptions in the social field for citizenship, arising from the subject of rights and duties. The aim of the article is to analyze the fundamentality of the normative and guaranteeing premises of the right to education, the construction of knowledge allied to human rights and the preparation of professionals for citizenship education. The methodology adopted for the research was of a qualitative nature, of the descriptive type, based on doctrines pertinent to the theme and current legislation for the deepening of reflection. Nowadays, the debate about the educational context is of paramount importance for teaching didactics and citizen education, in favor of the dignity of the human person, the precept of human rights, based on the emancipatory approach of subjects, in the social field of collective experiences, to the consolidation of the valorization of the directive values ​​listed in the Universal Declaration of Human Rights and affirmed in the Federal Constitution of 1988, with a guaranteeing precept for education through the Law of Guidelines and Bases for National Education.